2014
DOI: 10.1159/000363773
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Effect of Sunitinib and Immature Blood Vessels in Metastatic Renal Cell Cancer

Abstract: Introduction: This study was conducted to investigate the relationships between the effect of sunitinib and immature microvessels which are not covered by pericytes. Materials and Methods: This study involved 29 patients with clear-cell renal cell carcinoma (RCC) who took sunitinib after radical nephrectomy or biopsy due to metastatic RCC. Associations among clinicopathological factors, responses to sunitinib, and patient survival were reviewed. CD31 was used to stain endothelial cells, and anti-α-smooth muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…If this assumption is correct, one might reasonably expect this combination therapy to produce particularly obvious benefits in RETmut MTCs than in those without these mutations. Indirect support for this hypothesis has emerged from a recent study on metastatic clear-cell renal cell carcinomas, which showed that the subset of tumors whose vasculatures displayed high pericyte coverage tumors responded better than tumors without this feature to treatment with sunitinib, a multikinase inhibitor with strong effects on both PDGFRb and VEGFRs (Kim et al 2014). Additional preclinical evidence is needed, however, before this hypothesis can be adequately evaluated.…”
Section: :8mentioning
confidence: 99%
“…If this assumption is correct, one might reasonably expect this combination therapy to produce particularly obvious benefits in RETmut MTCs than in those without these mutations. Indirect support for this hypothesis has emerged from a recent study on metastatic clear-cell renal cell carcinomas, which showed that the subset of tumors whose vasculatures displayed high pericyte coverage tumors responded better than tumors without this feature to treatment with sunitinib, a multikinase inhibitor with strong effects on both PDGFRb and VEGFRs (Kim et al 2014). Additional preclinical evidence is needed, however, before this hypothesis can be adequately evaluated.…”
Section: :8mentioning
confidence: 99%
“…Although a therapy targeting VEGF receptors on immature neovessels in tumors has attracted attention as a new approach for antiangiogenic therapy , its therapeutic effect is insufficient because of abnormal induction of pericytes in tumor tissue. In RCC, the overall response rate to sunitinib has been reported to be greater in the high‐pericyte‐coverage group than in the low‐pericyte‐coverage group . Additionally, increased extracellular matrices in solid tumors elevate interstitial pressure, in turn reducing the tissue distributions of antitumor drugs which suggests the importance of the role of the PDGF‐receptor signaling pathway in controlling the interstitial pressure in tumors .…”
Section: Discussionmentioning
confidence: 99%